Cleavage Site Specificity and Conformational Selection in Type I Collagen Degradation - Salsas-Escat, Ramon; Nerenberg, Paul S; Stultz, Collin M (Biochemistry (Easton), 2010)
Excessive degradation of type I collagen is associated with a variety of human diseases such as arthritis, tumor metastasis, and atherosclerosis. Methods that further our understanding of collagenolysis may therefore provide insights into the mechanism of several important disorders. Prior experiments suggest that cleavage of collagen in vitro requires intact full-length collagenase, a multidomain protein containing both a catalytic and a hemopexin-like domain. In this work we demonstrate that type I collagen can be degraded at room temperature, a temperature well below the melting temperature of type I collagen, by collagenase deletion mutants that only contain the catalytic domain of the enzyme. Furthermore, these mutant enzymes hydrolyze the same peptide bond that is recognized by the corresponding full-length enzymes. Hence enzyme specificity at room temperature is achieved without the hemopexin-like domain. We demonstrate that these findings can be explained in light of a conformational selection mechanism that dictates that collagenases preferentially recognize and cleave preformed partially unfolded states of collagen.